2012
DOI: 10.1123/jsep.34.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stereotypes and Observer Pressure on Athletic Performance

Abstract: Although the effects of negative stereotypes and observer pressure on athletic performance have been well researched, the effects of positive stereotypes on performance, particularly in the presence of observers, is not known. In the current study, White males watched a video either depicting Whites basketball players as the best free throwers in the NBA (positive stereotype), Black basketball players as the best free throwers in the NBA (negative stereotype), or a neutral sports video (control). Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…As outlined in the coping with RWC pressure and avoiding the choke themes, the All Blacks appeared to have successfully countered similar stereotype pressures at the 2011 RWC. Indeed, one could argue that the 2011 All Blacks turned the negative stereotype pressure on its head and directly primed a positive stereotype by embracing the pressure and focusing on being your best, which generated a stereotype lift (Beilock & McConnell, 2004;Krendl, Gainsburg, & Ambady, 2012). Furthermore, one could argue that the close win (8-7) in the 2011 RWC final was a clutch performance (i.e., superior performance that occurs under pressure circumstances; Otten, 2009) and that this clutch performance was in large part due to the All Blacks coaches developing choking-resistant players (Mesgano & Marchant, 2013) who embraced the pressure via reappraisal (Balk et al, 2013;Otten, 2009) and benefited from a stereotype lift at the 2011 RWC tournament.…”
Section: Stereotype Threat and Stereotype Liftmentioning
confidence: 99%
“…As outlined in the coping with RWC pressure and avoiding the choke themes, the All Blacks appeared to have successfully countered similar stereotype pressures at the 2011 RWC. Indeed, one could argue that the 2011 All Blacks turned the negative stereotype pressure on its head and directly primed a positive stereotype by embracing the pressure and focusing on being your best, which generated a stereotype lift (Beilock & McConnell, 2004;Krendl, Gainsburg, & Ambady, 2012). Furthermore, one could argue that the close win (8-7) in the 2011 RWC final was a clutch performance (i.e., superior performance that occurs under pressure circumstances; Otten, 2009) and that this clutch performance was in large part due to the All Blacks coaches developing choking-resistant players (Mesgano & Marchant, 2013) who embraced the pressure via reappraisal (Balk et al, 2013;Otten, 2009) and benefited from a stereotype lift at the 2011 RWC tournament.…”
Section: Stereotype Threat and Stereotype Liftmentioning
confidence: 99%
“…Again, most research regarding the effect of ST on sensorimotor performance has observed debilitating effects. Studies have reported debilitation from ST in a variety of sensorimotor tasks such a golf putting task (Beilock, Jellison, Rydell, McConnell, & Carr, 2006; Stone, Lynch, Sjomeling, & Darley, 1999; Stone & McWhinnie 2008), soccer dribbling (Chalabaev, Sarrazin, Stone, & Cury, 2008; Heidrich & Chiviacowsky, 2015), simulated driving (Yeung & von Hippel, 2008), tennis serving (Hively & El-Alayli, 2014), and basketball free throw shooting (Hively & El-Alayli, 2014; Krendl, Gainsburg, & Ambady, 2012). The majority of these studies examined the effects of a gender-related ST, commonly reporting that female performance is debilitated when exposed to the stereotype that females perform worse than males either in athletic performance or in that specific motor task (Chalabaev et al, 2008; Heidrich & Chiviacowsky, 2015; Hively & El-Alayli, 2014; Stone & McWhinnie 2008; Yeung & von Hippel, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While less commonly studied, it has also been shown that male performance in a golf putting can be debilitated when instructed that females perform this task better than males (Beilock et al, 2006). In addition, evoking race-related stereotypes has led to debilitated sensorimotor performance in the stigmatized group (Krendl et al, 2012; Stone et al, 1999). These reports are consistent with the pervasive stereotype that males are more competent in athletics (Jacobs, Lanza, Osgood, Eccles, & Wigfield, 2002) and reach higher levels of daily physical activity (Knisel, Opitz, Wossmann, & Keteihuf, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords: stereotype threat, stereotype lift, rate of force development, maximal voluntary contraction, avoidance processes An emerging body of research indicates that stereotypes may be an important factor in athletic performance. Based on stereotype threat theory (Steele, 1997), these studies provided evidence that activating negative stereotypes may disrupt stereotyped individuals' performance on complex sensorimotor tasks, such as a golf-putting task (Beilock, Jellison, Rydell, McConnell, & Carr, 2006;Beilock & McConnell, 2004;Stone, Lynch, Sjomeling, & Darley, 1999;Stone & McWhinnie, 2008), a soccer-dribbling task (Chalabaev, Sarrazin, Stone, & Cury, 2008), and a free-throw basketball task (Krendl, Gainsburg, & Ambady, 2012).…”
mentioning
confidence: 99%